Adaptation of the pension system to demographic changes using the example of the republic of Tatarstan ("Journal "U". Economy. Management. Finance.", 2024)
This article presents an analysis of the pension system in the Republic of Tatarstan and suggestions for its adaptation to demographic changes. The role of actuarial calculations in forming the Long-Term Pension Development Strategy and conducting pension reforms has been studied. The aim of this article is to analyze the existing pension system in the Republic of Tatarstan in order to formulate proposals for its adaptation to demographic changes. To achieve this goal, the following tasks were set: studying and analyzing demographic trends in the Republic of Tatarstan and their impact on the pension system; reviewing existing pension mechanisms in the region, identifying risks and challenges faced by the pension system in connection with demographic changes. The results can be used to develop measures for adapting the pension system to new demographic realities.
Keywords: pension provision; actuarial calculations; demography; pension age; changes in the pension system